A pilot retrospective CT angio study of the internal pudendal arteries in male bodies, for the purpose of penis transplantation to trans men. Issue 2 (1st April 2022) - Selvaggi, Gennaro; Manner, Kristiina; Sakinis, Augustinas; Olausson, Michael
Abstract: Literature reports four successful cases where penile transplantation has been performed for cis men. To date, no penis transplantation has ever been attempted for trans men. Modern surgical techniques for penis reconstruction for (trans) men with gender incongruence present multiple drawbacks, and sometimes fail to meet patients' expectations. Penis transplantation could represent an alternative solution. With the aim of planning penis transplantation to trans men, a previous study from our same group suggested a surgical technique for explantation of penis and associated vessels, nerves and urethra en-bloc from a cadaver: further radiographic imaging of vascular anatomy was recommended. To measure length and diameter of the internal pudendal arteries at three set points in biological males, in order to confirm its viability for transplantation. A retrospective examination of existing CT images visualizing the internal pudendal arteries in 12 bodies, assigned male at birth, was performed. Diameters were measured in three points: 1. the take off of the artery; 2. distal to its rectal branch; and, 3. at the bifurcation of the two terminal branches of the artery, i.e. the bulbourethral artery and the dorsal artery of the penis. Mean diameters of the selected points were 2.4 mm, 1.9 mm, and 1.5 mm on both sides. Mean lengths of internal pudendal arteries were 111.2 mm on the left, and 120.1 mm on the right side. Diameters of the internal pudendal artery is sufficient for arterial anastomosis at all measured points. Lengths are sufficient to reach recipient vessels.